2002
DOI: 10.1161/01.atv.0000022889.85440.79
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Influences on Lipids, Lipoproteins, and Apolipoproteins

Abstract: Objective-Levels of lipids and (apo)lipoproteins are known to increase after menopause, but it is unknown whether the genetic and environmental variability alters or whether lipids and (apo)lipoproteins are influenced by different genes before and after menopause. Methods and Results-We studied 453 monozygotic and 1280 dizygotic pairs of female white twins recruited from the St. Thomas' UK Adult Twin Registry and measured total cholesterol, low density lipoprotein (LDL), high density lipoprotein (HDL), triglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
36
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 25 publications
11
36
1
Order By: Relevance
“…A subsample of twins underwent an oral glucose tolerance test for which glucose and insulin levels were measured before and 2 h after a 75-g oral glucose load. Levels of HDL cholesterol and triglycerides were measured using a Cobas Fara machine (Roche Diagnostics) (25). SBP and diastolic blood pressure (DBP) were measured twice using an automated cuff sphygmomanometer (OMRON HEM713C) and averaged over the two readings.…”
Section: Methodsmentioning
confidence: 99%
“…A subsample of twins underwent an oral glucose tolerance test for which glucose and insulin levels were measured before and 2 h after a 75-g oral glucose load. Levels of HDL cholesterol and triglycerides were measured using a Cobas Fara machine (Roche Diagnostics) (25). SBP and diastolic blood pressure (DBP) were measured twice using an automated cuff sphygmomanometer (OMRON HEM713C) and averaged over the two readings.…”
Section: Methodsmentioning
confidence: 99%
“…Menopause was found to be associated with an increase in TC and TG levels [32,33] and a decrease in HDL-C [8,34]. However, not all studies [8,12,29,35] agree with this conclusion.…”
Section: Biomed Research Internationalmentioning
confidence: 97%
“…We found that mean systolic blood pressure and pulse pressure were higher in postmenopausal women than premenopausal women after adjusting for age. Menopause is associated with an increase in total and LDL cholesterol and triglyceride levels (21,27), while HDL cholesterol level decreases with menopause (28,29). However, not all studies (28,30) agree with this conclusion.…”
Section: Conclusion -A Higher Prevalence Of the Metabolic Syndrome Amentioning
confidence: 99%